Team psychology in sports : theory and practice - Cotterill, Stewart (Abingdon, Oxon : Routledge, 2013)
"The ability to mould a group of talented individual athletes into an effective team takes effort and skill. Team Psychology in Sports examines the crucial factors in the development of an effective team, introducing important psychological and organizational concepts and offering evidence-based interventions for enhancing the performance of any sports team. The book neatly bridges the gap between theory and practice, with real sporting case studies, examples and practical tools included in each chapter. It covers the full range of issues in team sport, including: - planning - communication - cohesion - motivation - emotions - momentum - leadership - recovery. No other book offers such an up-to-date, relevant and applied guide to working with sports teams. It is essential reading for all students and practitioners working in sport psychology or sports coaching" -- Provided by publisher
1. Introduction -- 2. Team planning and effectiveness -- 3. Developing a positive team environment -- 4. Role clarity and role acceptance -- 5. Developing effective team communication -- 6. Cohesion in sport -- 7. Motivating the team -- 8. Managing emotions in team sports -- 9. Momentum in sport -- 10. Effective team leadership -- 11. Mental and Emotional Recovery
Includes bibliographical references (p. [146]-165) and index
Keywords: Sports teams -- Psychological aspects; Sports -- Psychological aspects; Teamwork (Sports) -- Psychological aspects